RTOS Based Fault Diagnosis And Efficient Data Transfer On Priority Basis Using Can (International Journal of Engineering and Computer Science, 2017)
—CAN protocol is a broadcast communication protocol and it is used for automotive application. CANalyzer is a software tool which is used for analysis and stimulation of bus communication. It is used to check whether and what type of communication is occurring on the bus. It is used to send or log data. CANalyzer is a high cost tool and it is not suitable for small applications. This paper demonstrates the implementation of priority based message transfer using CAN protocol and also demonstrates the faulty messages in the system without using CANalyzer. The system uses µC/OS II RTOS and ARM.